2020
DOI: 10.1186/s12906-020-02893-9
|View full text |Cite
|
Sign up to set email alerts
|

“Inhibitory effect of Brazilian red propolis on Candida biofilms developed on titanium surfaces”

Abstract: Background: Peri-implant inflammation resulting from the presence of Candida biofilms may compromise the longevity of implant-supported dentures. This study evaluated the inhibitory effect of Brazilian red propolis on mono-species biofilms of C. albicans (ATCC 90028) and co-culture biofilms of C. albicans (ATCC 90028) and C. glabrata (ATCC 2001), developed on titanium surfaces. Methods: Titanium specimens were pre-conditioned with artificial saliva and submitted to biofilm formation (1 × 10 6 CFU/mL). After 24… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 37 publications
1
11
0
Order By: Relevance
“…In general, the antimicrobial results displayed by EGP and ERP agree with data previously reported in the literature describing the potent antimicrobial activity of BRP and moderate to the weak antimicrobial potential of green propolis [23,27] . Moreover, these data agree with the literature emphasis that propolis extracts are more effective against Gram‐positive bacteria [8,9,11,28] .…”
Section: Resultssupporting
confidence: 90%
“…In general, the antimicrobial results displayed by EGP and ERP agree with data previously reported in the literature describing the potent antimicrobial activity of BRP and moderate to the weak antimicrobial potential of green propolis [23,27] . Moreover, these data agree with the literature emphasis that propolis extracts are more effective against Gram‐positive bacteria [8,9,11,28] .…”
Section: Resultssupporting
confidence: 90%
“…Propolis extracts also effectively eradicated biofilms formed by other dangerous bacteria, such as P. aeruginosa [ 30 , 31 , 32 ] and pathogenic fungi such as Candida spp. [ 33 , 34 , 35 ]. Our analysis of the literature has shown that another important problem that remains unresolved is the selection of appropriate methods for studying biofilm formation and assessing the effectiveness of antimicrobial agents in biofilm eradication.…”
Section: Discussionmentioning
confidence: 99%
“…Initially, titanium discs were immersed in 500 µL of artificial saliva composed of 1% carboxymethyl (w/v); 0.0084% sodium chloride (w/v); 0.12% potassium chloride (w/v); 0.0342% potassium phosphate (w/v); 0.0146% calcium chloride (w/v), and 0.052% magnesium chloride (w/v) [ 18 , 19 ]; following by incubation at 37 °C for 60 min [ 20 ]. Subsequently, the specimens were randomly and individually allocated into 24-well plates.…”
Section: Methodsmentioning
confidence: 99%
“…For co-culture biofilms, both C. albicans and S. salivarius were added to the inoculum. The plates were incubated at 37 °C under a micro-aerobic atmosphere using an anaerobic jar with a candle, which reduced the presence of oxygen, similar to a peri-implantitis-like microenvironment [ 20 ]. The culture medium was changed daily until the end of the experimental period (72 h).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation